ANALISIS PENYEBAB PERILAKU MENYIMPANG TERLAMBAT PADA SISWA SMA NEGERI 4 SUNGAI RAYA - Siti Sulistia Pratiwi; Rustiyarso Rustiyarso; Imran Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study was an analysis on the causes of coming late behavior of students of SMAN 4 Sungai Raya. The general problem of this study was why do the students of SMAN 4 Sungai Raya commit this coming late behavior. The specific problems are (1) What causes the students of SMAN 4 Sungai Raya commit coming late behavior from the internal factor. (2) What causes the students of SMAN 4 Sungai Raya commit coming late behavior from the external factor. This study aims to know and describe the causes of coming late behavior from the internal and external factors. The method used in this study was qualitative with descriptive analysis. The tools of data collecting are observation guide, interview guide, and documentation. The result of this study were (1) Based on the the internal factor, the cause commit coming late behavior of students of SMAN 4 Sungai Raya are they have ignored the school regulation. (2) Based on the external factor, the cause commit coming late behavior of students of SMAN 4 Sungai Raya are they less of their parents attention, they get bad influence from theit friends who commit coming late, and they break the school rules.Keywords : Coming Late to School, Student, The Cause of Deviant Behavior